Guenzet for a sustainable tourism revival - Ababsa, Hadjer; Samaï-Bouadjadja, َAssia (Journal of Architecture and environment of child, 2025)
Guenzet is situated in a mountainous region with significant heritage potential. It embodies an exceptional harmony between the vernacular built environment and its natural surroundings. Despite the importance of its environmental, economic, social, and cultural potentials, its population continues to decline. This article focuses on the remarkable tangible and intangible heritage of this locality, which seemingly extends to the entire mountainous part of Algeria, referred to as "Little Kabylie": oral culture, clothing, culinary art, artisanal practices and skills, vernacular architecture, etc. This heritage reflects an ancestral culture dating back to the establishment of the Béni-Yaala. It is noteworthy that today, this heritage is recognized by all segments of the population. As evidence, we cite the festivals of the two traditional dishes "Tikorbabine" and "Chlita," which are found only in the Guenzet region, organized by the resilient women's association every last week of August. Moreover, data collected through a survey based on direct observation and non-directive interviews conducted on a random sample consisting of local elected officials and ordinary citizens demonstrate the resilience of the Guenzetis and their readiness to undertake projects likely to stimulate the local economy and consequently encourage inhabitants to return to their lands. لإhe objective of this study is to highlight this abundant yet endangered heritage, in favor of a sustainable tourism project in the broadest sense: environmentally respectful, equitable, and stimulating the economic development of Guenzet